Copper‐Catalyzed Synthesis of Trinuclear N‐Fused Hybrid Scaffolds by Double C(sp2)–N Bond Formation between 2‐(2‐Bromoaryl)indoles and 2‐Aminoazoles. Issue 19 (24th March 2020) - Diep, Thi Duyen; Duy Quang Dao, Pham; Ho, Son Long; Cho, Chan Sik
Abstract : 2‐(2‐Bromoaryl)indoles react with 2‐aminoazoles by microwave irradiation in DMF in the presence of a catalytic amount of CuI and a base to produce trinuclear N‐fused hybrid scaffolds, benzo[4, 5]imidazo[1, 2‐ a ]indolo[1, 2‐ c ]quinazolines and imidazo[1, 2‐ a ]indolo[1, 2‐ c ]quinazolines in moderate to good yields. The reaction seems to proceed via copper‐catalyzed C( sp 2 )‐N coupling and subsequent intramolecular cyclocondensation accompanied by ammonia evolution. Complete regioselective C–N cyclization is observed with the reaction of 2‐(2‐bromophenyl)indole with 2‐aminoazoles. Abstract : A promising synthetic method for indole‐quinazoline‐benzimidazole and indole‐quinazoline‐imidazole trinuclear N‐fused hybrid scaffolds has been developed by copper‐catalyzed C( sp 2 )‐N coupling and cyclization of 2‐(2‐bromoaryl)indoles with 2‐aminoazoles as new building blocks. Further challenges on the construction of polynuclear N‐fused hybrid scaffolds using 2‐aminoazoles are expected.